Facts about the General Medical Care of Adults with Congenital Heart Defects: Experience of a Tertiary Care Center - Seidel, Lavinia; Nebel, Kathrin; Achenbach, Stephan; Bauer, Ulrike; Ewert, Peter; Freilinger, Sebastian; Gundlach, Ulrike; Kaemmerer, Harald; Nagdyman, Nicole; Oberhoffer, Renate; Pieper, Lars; Reinhard, Wibke; et al. (Journal of Clinical Medicine, 2020)
Background: Due to the increase in survival rates for congenital heart disease (CHD) in the last decades, over 90% of patients today reach adulthood. Currently, there are more than 300,000 adults with CHD (ACHD) living in Germany. They have an increased need for specialized medical care, since almost all ACHD have chronic heart disease and suffer from specific chronic symptoms, risks, and sequelae. Primary care physicians (PCPs) play a crucial role in referring patients to ACHD specialists or specialized institutions. This cross-sectional study is intended to clarify the real-world care of ACHD from the PCP's perspective.Methods:This analysis, initiated by the German Heart Centre Munich, was based on a 27-item questionnaire on actual ACHD health care practice in Germany from the PCP's perspective.Results: In total, 767 questionnaires were considered valid for inclusion. The majority of the PCPs were general practitioners (95.9%), and 84.1% had cared for ACHD during the past year. A majority (69.2%) of the PCPs had cared for patients with simple CHD, while 50.6% and 33.4% had cared for patients with moderate and severe CHD, respectively, in all age groups. PCPs treated almost all typical residual symptoms and sequelae, and advised patients regarding difficult questions, including exercise capacity, pregnancy, genetics, and insurance matters. However, 33.8% of the PCPs did not even know about the existence of certified ACHD specialists or centers. Only 23.9% involved an ACHD-specialized physician in their treatment. In cases of severe cardiac issues, 70.8% of the PCPs referred patients to ACHD-certified centers. Although 52.5% of the PCPs were not sufficiently informed about existing structures, 64.2% rated the current care situation as either "very good" or "good". Only 26.3% (n= 190) of the responding physicians were aware of patient organizations for ACHD.Conclusions: The present study showed that the majority of PCPs are not informed about the ACHD care structures available in Germany. The need for specialized ACHD follow-up care is largely underestimated, with an urgent need for optimization to reduce morbidity and mortality. For the future, solutions must be developed to integrate PCPs more intensively into the ACHD care network.
CRIS-Team WoS Importer:2020-07-31